Wound Healing Using Electrical Stimulation: A Review - Farah Jala Jaseem; Jameel Kadhim Abed; Ahmed Rashid Ajel; Noaman Mohammad Noaman (Journal of Techniques)
The wound healing process is considered one of the most important elements of progress in the health and medical reality alike, because it has a direct impact on the patient’s life, especially those who suffer from chronic diseases such as diabetes mellitus and others. All over the world, especially in developing countries, many people are exposed to afflictions due to the lack of ability to heal wounds or the delay in their recovery. The healing of wounds is always attributed to the ability of the affected skin to produce an electric current that helps the migration of stem cells and platelets to the place of extraction For the sake of healing, this is why electrical stimulation ES devices played an important role in the process of stimulation and wound treatment through using the high voltage pulsed current HVPC, low voltage pulsed current LVPC, direct current DC or pulse current PC. In this study, we review some of the important works that touched on this field in terms of the aim of their studies and the outcome that was reached, and the results were extracted. We also discuss the problems that faced researchers, especially those problems that Their studies miss it.